5 Worlds: The Emerald Gate - Book 5 Book 5, The emerald gate - Siegel, Mark, 1967-; Siegel, Alexis; Bouma, Xanthe; Rockefeller, Matt; Sun, Boya (New York : Random House, 2021)
"In the epic conclusion to the 5 Worlds series, the final battle looms as Oona, Jax, and An Tzu travel to the treacherous world of Grimbo (E)! There, Oona must light the last beacon to save the 5 Worlds, but first she has to find it! When Jax saves an old friend, Oona is given a clue to the green beacon's location. Unfortunately, the journey to lighting it on this strange, watery planet is the most dangerous yet. Meanwhile, Stan Moon has one more trick up his sleeve as his frightening powers and mysterious connection to An Tzu continue to grow. How can Oona ever hope to beat him? Can she count on her friends or will a terrible betrayal mean the 5 Worlds will be lost to evil forever?"--
Keywords: Heroes -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Heroes -- Fiction; Good and evil -- Fiction; Adventure and adventurers -- Fiction; Science fiction; Comics (Graphic works); Adventure comics